Teaching Law Students of Non-Legal Professions as a Subject of Scientific Research - Budas, Anna (Pedagogical Discourse, 2014)
The specificity of law teaching methods students of non-legal professions has been defined, and the basic approaches to the selection of methods, means and organizational forms of teaching the science of law to meet its objectives and content have been characterized. On the basis of the competence approach the meaning of the term «law teaching methods» has been specified and its components have been specified. The importance of the aims giving phase in the law teaching has been emphasized and it also has been defined, that the main goal of the law teaching is to form the legal experience, and to give to students the system of skills, particularly those, that related to the normative regulation of their professional activity. The author of the article came to the conclusion that the methodology of law teaching is a dynamic science due to the changes of the legislation, the development of the jurisprudence, and the transformation of the level of the society legal culture. The key criteria for selecting the law teaching methods for the students of non-legal professions have been formulated.